Histamine 1 Receptor Blockade Enhances Eosinophil-Mediated Clearance of Adult Filarial Worms - Fox, Ellen Mueller; Morris, Christopher P.; Hübner, Marc P.; Mitre, Edward (PLOS Neglected Tropical Diseases, 2015)
Author Summary Filariae are tissue-invasive parasitic roundworms that infect over 100 million people worldwide and cause debilitating conditions such as river blindness and elephantiasis. One of the major factors limiting our ability to eliminate these infections is the lack of drugs that kill adult worms when given as a short course therapy. Additionally, the mechanisms by which adult worms are cleared from infected individuals remains poorly understood. In this study, we demonstrate that treatment of infected mice with fexofenadine, an inhibitor of histamine receptor 1, significantly reduces adult worm numbers through a mechanism dependent on host eosinophils. These findings suggest that histamine release induced by parasitic worms may aid parasite survival by decreasing eosinophilic responses. Further, as antihistamines are generally safe medications, these results raise the possibility that antihistamine therapy may be useful either alone, or potentially in combination with other antifilarial medications such as diethylcarbamazine (DEC), to eliminate adult filarial worms from infected individuals.